EFFECTIVE WAYS OF MANAGING WEBSITES FOR ACADEMIC INSTITUTIONS - Răduică, Florin Felix; Enache, Cătălina; Simion, Ionel (PEOPLE: International Journal of Social Sciences, 2019)
The paper describes the process of building and developing a proper website for academic institutions. Development needs to follow certain guidelines like planning a good structure and writing quality content in order to be able to convey the information that needs to be delivered to the target audience. The study surveyed existing higher education institutions websites from the current best top 100 list by QS World University Rankings. Although the scale is different the audience is the same and the structure of the websites does not differ. We found that educational websites keep a similar structure, but some manage to present the information in a much subtle manner to their audience. One of the most important features of an academic website is to make information accessible to all. The authors used a documentation review as a means of surveying to gather information about university websites. The purpose being to make informed recommendations about the best practices used in higher education website development. In conclusion we found that information needs to be displayed clearly, we recommend contact information to be placed on the front page as well as relevant information about the institution.